Paradoxes of adherence and drug resistance to HIV antiretroviral therapy - David R. Bangsberg; Andrew R. Moss; Steven G. Deeks (2004)
Public health debates about providing HIV antiretroviral therapy to impoverished populations have centred on the relationship between adherence and risk of drug resistance. Recent data indicate that each antiretroviral therapeutic class has a unique adherence–resistance relationship. Resistance to single protease inhibitor therapy occurs most frequently at moderate to high levels of adherence, resistance to non-nucleoside reverse transcriptase inhibitor therapy occurs at low to moderate levels of adherence, and resistance to ritonavir-boosted protease inhibitor therapy is most likely to occur at middle ranges of adherence. These dynamic relationships should be considered in balancing the individual and public health benefits of therapy.